2012
DOI: 10.1152/ajpgi.00341.2012
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of gut microbiota in the production of biologically active, free catecholamines in the gut lumen of mice

Abstract: There is increasing interest in the bidirectional communication between the mammalian host and prokaryotic cells. Catecholamines (CA), candidate molecules for such communication, are presumed to play an important role in the gut lumen; however, available evidence is limited because of the lack of actual data about luminal CA. This study evaluated luminal CA levels in the gastrointestinal tract and elucidated the involvement of gut microbiota in the generation of luminal CA by comparing the findings among speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
406
2
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 535 publications
(432 citation statements)
references
References 53 publications
10
406
2
14
Order By: Relevance
“…As a bacterial adrenergic receptor, QseC senses the host stress molecules NE and EPI and activates a signaling cascade that induces virulence gene expression (20). Thus, we evaluated the effects of qseC inactivation on CA-induced flagellar gene expression in the parental and ΔqseC mutant strains and selected NE rather than EPI because NE is more abundant in the intestinal lumen (28). NE up-regulated the expression of quorum-sensing and flagellar genes in the parental strain, but not in ΔqseC ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a bacterial adrenergic receptor, QseC senses the host stress molecules NE and EPI and activates a signaling cascade that induces virulence gene expression (20). Thus, we evaluated the effects of qseC inactivation on CA-induced flagellar gene expression in the parental and ΔqseC mutant strains and selected NE rather than EPI because NE is more abundant in the intestinal lumen (28). NE up-regulated the expression of quorum-sensing and flagellar genes in the parental strain, but not in ΔqseC ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond their role as host stress hormones, CAs are also produced by the enteric nervous system and are important for regulating intestinal motility, electrolyte transport, and immune homeostasis (27). Moreover, evidence that levels of biologically active CAs in the intestinal lumen require specific bacterial-encoded enzymes suggests that luminal CA levels are gut microbiota-dependent (28). CAs continue to attract interest as communication molecules between host cells and microbes; these stress signals may influence microbial dysbiosis and increase the susceptibility to infection by altering the growth and virulence of human pathogens, including Enterobacteriaceae species (29,30).…”
mentioning
confidence: 99%
“…Tsavkelova et al (180) , identified a wide range of bacteria, which produce mmol quantities of dopamine (180) and which could be used for the treatment of Parkinson's disease, Alzheimer's disease and other major depressive disorders whereby dysfunctions in catecholamine neurotransmission are implicated. In addition, bacteria which constitute the normal gut microbiome in mice have been shown to be capable of the production of norepinephrine in vivo (181) . Acetylcholine is a neurotransmitter found in the CNS and peripheral nervous system which plays a critical role in cognitive function, particularly in memory and learning.…”
Section: Catecholamines and Acetylcholinementioning
confidence: 99%
“…Although it remains to be established whether the microbiota can produce neuropeptide-like compounds, they are capable of generating a number of neurotransmitters and neuromodulators [7,14]. Members of the genera Candida, Streptococcus, Escherichia and Enterococcus synthesize 5-hydroxytryptamine (5-HT), members of the genera Escherichia, Bacillus and Saccharomyces generate dopamine and/or noradrenaline, members of the genus Lactobacillus produce acetylcholine, and members of the genera Lactobacillus and Bifidobacterium manufacture gamma-aminobutyric acid (GABA) [7,14,[36][37][38][39]. The release of microbiota-derived dopamine into the lumen of the intestine has been suggested to play a proabsorptive role in the colon [38].…”
Section: Neuroactive Factors Released By the Gut Microbiotamentioning
confidence: 99%
“…Members of the genera Candida, Streptococcus, Escherichia and Enterococcus synthesize 5-hydroxytryptamine (5-HT), members of the genera Escherichia, Bacillus and Saccharomyces generate dopamine and/or noradrenaline, members of the genus Lactobacillus produce acetylcholine, and members of the genera Lactobacillus and Bifidobacterium manufacture gamma-aminobutyric acid (GABA) [7,14,[36][37][38][39]. The release of microbiota-derived dopamine into the lumen of the intestine has been suggested to play a proabsorptive role in the colon [38]. Signalling via opioid and cannabinoid receptors may also be modified by the gut microbiota, a conclusion based on the ability of certain probiotics to alter the expression of opioid and cannabinoid receptors in the gut [7].…”
Section: Neuroactive Factors Released By the Gut Microbiotamentioning
confidence: 99%